2013
DOI: 10.1093/humupd/dms053
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-colony stimulating factor for hematopoietic stem cell donation from healthy female donors during pregnancy and lactation: what do we know?

Abstract: BACKGROUND Hematopoietic growth factors (HGFs) are mostly used as supportive measures to reduce infectious complications associated with neutropenia. Over the past decade, the use of HGFs became a common method for mobilizing human CD34+ stem cells, either for autologous or allogeneic transplantation. However, since their introduction the long-term safety of the procedure has become a major focus of discussion and research. Most information refers to healthy normal donors and data concerning pregnant and lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…The colony-stimulating factors delay neutrophil death [ 31 ]. While G-CSF influences proliferation and differentiation of neutrophil progenitor cells as well as the function of mature neutrophils, GM-CSF often appears in the context of recruitment, activation, and survival of eosinophils [ 38 , 49 ]. Concerning G-CSF, we found levels threefold higher in NP than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…The colony-stimulating factors delay neutrophil death [ 31 ]. While G-CSF influences proliferation and differentiation of neutrophil progenitor cells as well as the function of mature neutrophils, GM-CSF often appears in the context of recruitment, activation, and survival of eosinophils [ 38 , 49 ]. Concerning G-CSF, we found levels threefold higher in NP than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Granulocyte-colony-stimulating factor (G-CSF, filgrastim) is the most commonly used colony stimulating factor. It is usually used (1) in patients with neutropenia to reduce the incidence of infectious complications, and (2) for mobilization of stem cells in donors of autologous and allogeneic HSCT [118]. The administration of G-CSF in pregnant women who serve as donors for HSCT is generally safe as data from 5 studies that included HSCT donors including pregnant females did not show any evidence of increased risk of leukemogenicity [118].…”
Section: Growth Factors In Pregnancymentioning
confidence: 99%
“…It is usually used (1) in patients with neutropenia to reduce the incidence of infectious complications, and (2) for mobilization of stem cells in donors of autologous and allogeneic HSCT [118]. The administration of G-CSF in pregnant women who serve as donors for HSCT is generally safe as data from 5 studies that included HSCT donors including pregnant females did not show any evidence of increased risk of leukemogenicity [118]. Also, data from 8 studies that included 96 pregnant females having hematological malignancies showed delivery of 94 healthy babies, but one fetal death as the mother was exposed to idarubicin and cytarabine during pregnancy in addition to one birth of a child with low intelligence and malignancy [118].…”
Section: Growth Factors In Pregnancymentioning
confidence: 99%
“…(2) As soon as G-CSF became available, patients and physicians began asking about the benefits and safety of its administration during pregnancy, questioning its effects on the health of both the mother and the neonate, in part because administered G-CSF crosses the placenta. (3)…”
Section: Introductionmentioning
confidence: 99%